ERROR ANALYSIS OF SILENT LETTERS PRONUNCIATION MADE BY THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT STBA JIA - Elsan Arvian (Ennichi, 2021)
This research investigated the errors of English pronunciation on silent lettters by the fourth semester students of English Department STBA JIA. The focus of this research were 1) to find out errors of pronunciation made by the fourth semester students of STBA JIA, 2) to find out the causes of the error and 3) to find out the errors mostly exist in this case. This research combined theory from Carney (2012) and Crystal (2012) about silent letters, theory by Corder in Ellis (2008) about steps of error analysis, theory of phonotactic constraints of English from Brinton (2010) and Indonesian from Alwi et al (2017). Twenty students of English Department Programme at STBA JIA were assigned to pronounce 30 English words containing silent letters in the initial, medial, and final position of the word. The frequency of errors was calculated in percentage. In this research, the writer used descriptive qualitative method. The study revealed that: 1) the participants mostly made post-systematic errors 2) the most frequent word mispronounced by the students are honest in the initial position, sword in the medial position as well as ballet and bufffet in the final position. There were 145 errors made by the students with the percentage of 24.17% error. Among three positions of the occurrence, the medial position was the most frequent category of error with 63 errors (31.5%), followed by 53 errors in the final position (26.5%), and 29 errors in the initial position (14.5%). The participants? first language that is, the absence of the phonotactics constraints of both English and Indonesian and the lack of knowledge of students about the pronunciation of ancient English words are the causes of error. Keywords: Analysis, Error, Silent Letters.